PENGARUH KUALITAS PRODUK, KEBIJAKAN HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (STUDY KASUS PADA KONSUMEN DI MATAHARI DEPARTEMEN STORE TBK) - Naimmatun Nasiroh; Untung Widodo (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2017)
This study aims to determine the quality of products, pricing policies and promotion of purchasing decisions either partially or simultaneously to consumers in Matahari Department Store Tbk Semarang. The object of this research is consumer in Matahari Department Store Tbk Semarang. Data was collected in March 2017 with a questionnaire or questionnaire obtained from consumers at Matahari Department Store Tbk Semarang. Data analysis tools used are multiple linear regression analysis and significance test using t test and F test.The results showed that partially product quality and promotion have a significant influence on purchasing decision. But pricing policies have no significant partial effect on purchasing decisions. However, in the F test or simultaneous product quality, pricing and promotion policies have a significant effect on purchasing decisions